2016
DOI: 10.1111/ejn.13383
|View full text |Cite
|
Sign up to set email alerts
|

Virally delivered, constitutively active NFκB improves survival of injured retinal ganglion cells

Abstract: Since axon damage and retinal ganglion cell (RGC) loss lead to blindness, therapies that increase RGC survival and axon regrowth have direct clinical relevance. Given that NFκB signaling is critical for neuronal survival and may regulate neurite growth, we investigated the therapeutic potential of NFκB signaling in RGC survival and axon regeneration. Although both NFκB subunits (p65 and p50) are present in RGCs, p65 exists in an inactive (unphosphorylated) state when RGCs are subjected to neurotoxic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…Optic nerve crush (ONC) injury was performed on either male C57BL/6J WT or male Thy1-GFP mice at 2 months of age. The ONC procedure was performed as previously described [72]. Briefly, all mice were anesthetized via intraperitoneal injection of ketamine (80 mg/kg) / xylazine (10 mg/kg); their optic nerves were exposed intraorbitally and crushed with jeweler's forceps (Dumon #5; tip dimension, 0.1 x 0.6 mm) for 10 seconds approximately 1 to 2 mm behind the optic disk, pupillary response using indirect illumination from the side was used to indicate a successful injury.…”
Section: Optic Nerve Crush Model (Onc)mentioning
confidence: 99%
“…Optic nerve crush (ONC) injury was performed on either male C57BL/6J WT or male Thy1-GFP mice at 2 months of age. The ONC procedure was performed as previously described [72]. Briefly, all mice were anesthetized via intraperitoneal injection of ketamine (80 mg/kg) / xylazine (10 mg/kg); their optic nerves were exposed intraorbitally and crushed with jeweler's forceps (Dumon #5; tip dimension, 0.1 x 0.6 mm) for 10 seconds approximately 1 to 2 mm behind the optic disk, pupillary response using indirect illumination from the side was used to indicate a successful injury.…”
Section: Optic Nerve Crush Model (Onc)mentioning
confidence: 99%
“…In previous report, we suggested that Wnt/β-catenin signaling and Nf-κb protein are involved in the neuroprotection of R28 by MSCs [27,28]. In this study, we also examined whether Wnt/β-catenin signaling may be involved with NPC in the recovery mechanisms of damaged R28 cells.…”
Section: Wnt/β-catenin Signal Is Involved During Recovery Of Retinal Ganglion Cells By Npcsmentioning
confidence: 85%
“…The mechanisms by which MSCs directly regulate neuroprotection remain unclear. PSCs have neuroprotective effects via the moderation of Hif-1α and GAP43 [22] and mediation of NF-κb pathways [27,28]. These results suggest that MSC-based therapy may be useful for treating optic nerve disorders, but the critical pathway for optic nerve recovery is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…In prior work on RGC neuroprotection in vivo (Guo et al, 2021), the transcription factor CREB was implicated as necessary for CaMKIIα's neuroprotective effect, although the role of CREB in RGC neuroprotection is controversial (Pita-Thomas et al, 2021). Another potentially relevant CaMKII effector is the transcription factor nuclear factor-κB (NF-κB; Dvoriantchikova et al, 2016), as suggested by studies showing that the in vitro neuroprotective effects of CaMKIIγ and CaMKIIδ during oxygen/glucose deprivation and reoxygenation correlated with the activation of the NF-κB pathway (Ye et al, 2019). CREB is not likely the CaMKII effector responsible for the observed RGC axon growth suppression, as CaMKII inhibition blocked RGC axon outgrowth in vitro stimulated by oncomodulin and elevated cAMP, a treatment that also activates CREB (Yin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%